The intuitionist - Whitehead, Colson (Fleet, 2017)
An elevator inspector becomes the center of controversy when an elevator crashes. The inspector, Lila Mae Watson, is a black woman who inspects by intuition, as opposed to visual observation, and now she must prove her method was not at fault. A study of society's attitude to technology and a debut in fiction.